Topological encounters in biodiversity conservation: Making and contesting maps in the Colombian high Andean páramos - Castillo-Estupiñan, Camilo (Frontiers in Ecology and Evolution, 2023)
Páramos are one of the flagship ecosystems in the Northern Andes; the provision of water for millions of people in this region depends on these unique high mountains located at above 3,500 m of altitude. Besides, they are also the refuge of a rich biodiversity that is unique in the world, the conservation of which has become important in recent years. Human communities, such as campesino communities, have also inhabited some páramos. For example, in the Sumapaz region of central Colombia, campesino communities sought refuge in the páramos during the 20th century due to political violence. Since 2010, the Colombian government, following previous legislation and court sentences, has declared páramos “strategic ecosystems,” making their conservation a vital part of the environmental policy in the country. This was advanced through mapmaking as the tool to define clear-cut limits for human use, prohibiting mining, agriculture, and livestock in spaces demarcated as páramos. However, this made the conservation of the policy incompatible with the presence of campesinos living in páramos. Since then, their conservation in the Sumapaz region has been a contentious matter about what kind of páramos and biodiversity should be allowed and enacted in Colombia. As part of a two-year multi-sited ethnography with geographers and campesino communities in Sumapaz páramo, I developed a topological approach to study mapmaking practices in the context of biodiversity conservation. I argue that this can be a way to understand the diverse relations between humans and nature as partial space configurations that shape conservation practice and its forms of politics. With this social sciences contribution, I extend the mapmaking discussions in conservation that seek to open taken-for-granted notions of space that limit conservation possibilities for socioenvironmental change.